Study Effects Of Aqueous Extract Of Local Fenugreek Seeds And Olive Leaves In Some Biochemical Traits At Iraqi Awassi Sheep (Journal of Pharmaceutical Negative Results, 2022)
This study was conducted to determine the effect of using an aqueous extract of local fenugreek seeds and olive leaves on some of the biochemical traits of Iraqi Awassi sheep. Twenty Awassi sheep aged 11-12 months with an average weight of 48.50 kg were used in this study. The ewes of the experiment were divided into five transactions. The duration of the study reached four complete estrus cycles (70 days) with the addition of 14 days at the start of the experiment to unify estrus to make the total days of the experiment 84 days (12 weeks). The animals were randomly distributed into five equal groups with four repetitions in each group as follows: the first control treatment dosed the ewes with distilled water only, T2 the second treatment was dosed with fenugreek seed aqueous extract at a concentration of (25 mg/ ml/ kg), T3 the third treatment was dosed with fenugreek seed aqueous extract at a concentration of (50 mg/ ml/ kg), T4 the fourth treatment was dosed with olive leaf aqueous extract at a concentration of 25 mg/ ml/kg. T5, the fifth treatment, was dosed with an aqueous extract of olive leaves at a concentration of (50 mg/ml /kg). As for biochemical parameters, there was a least significant decreasing (P≤0.05) in blood glucose level in the third treatment and total period in comparing with all other treatments Over the duration of the experiment. T3 recorded a significant superiority (P≤0.05) in total protein compared to other treatment groups. Although there was a decreasing in total protein concentrations of T5 in the third, fourth and total periods compared to T3. No significant differences between all study groups at albumin level except in total period which T5 Outperformed control group. T2 and T3 were recorded significantly decreasing (P≤0.05) in AST and ALT compared to the control group, as for the T5 showed the lowest significant decrease was recorded in (P≤0.05) of all experimental withdrawals. In addition to the moral decline recorded by the ewes of the T4 group compared to the control group from the second withdrawal to the end of the experiment.